Estimating the relevance of predictions from the Skyrme–Hartree–Fock model. (28th December 2015) - Reinhard, P-G
Abstract: This contribution examines the predictive power of the Skyrme–Hartree–Fock (SHF) approach which is one of the leading self-consistent mean-field models in the physics of atomic nuclei. It starts with a brief summary of the formalism and strategy for proper calibration of the SHF functional. The main emphasis lies on an exploration of the reliability of predictions, particularly in the regime of extrapolations. Various strategies are discussed to explore the statistical and systematic errors of SHF. The strategies are illustrated on examples from actual applications. Variations of model and fit data are used to get an idea about systematic errors. The statistical error is evaluated in straightforward manner by statistical analysis based on χ 2 fits. This also allows one to evaluate the correlations (covariances) between observables which provides useful insights into the structure of the model and of the fitting strategy.